2022
DOI: 10.3390/ijerph19052919
|View full text |Cite
|
Sign up to set email alerts
|

Designing Environmental Messages to Discourage Red Meat Consumption: An Online Experiment

Abstract: Reducing red meat consumption in high-consuming countries is critical for mitigating climate change and preventing chronic disease. This study tested the effectiveness of messages conveying the worsening or reduction of environmental harms at discouraging red meat consumption. 1078 U.S. adults viewed seven messages in an online survey highlighting the reduction or worsening of environmental harms associated with eating red meat (between-subjects factor) and rated the messages on how much they discouraged them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 80 publications
(104 reference statements)
2
2
0
Order By: Relevance
“…Higher self-reported consumption of red meat was significantly associated with lower PME ratings for environmental messages. Again, this relationship between lower red meat consumption and higher PME for environmental messages was consistent with the recent study published by Wistar et al [75]. No such relationship between red meat intake and PME emerged for health messages.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Higher self-reported consumption of red meat was significantly associated with lower PME ratings for environmental messages. Again, this relationship between lower red meat consumption and higher PME for environmental messages was consistent with the recent study published by Wistar et al [75]. No such relationship between red meat intake and PME emerged for health messages.…”
Section: Plos Onesupporting
confidence: 92%
“…The exception to this pattern is that the environment message elicited higher PME than the carbon footprint, water shortage, and climate change messages. These results are consistent with a recently published study by Wistar et al which also found that a general environment message was perceived as more effective at discouraging red meat consumption than other environmental topics [75]. In contrast, it was surprising that the carbon footprint message elicited lower perceived message effectiveness as many existing environmental warning labels focus on carbon footprints.…”
Section: Plos Onesupporting
confidence: 91%
“…The second section focused on understanding the patterns of the diets. According to the literature [94], it was found that most of the Sapienza community is trying to decrease their consumption of red meat, and, at the same time, most of them followed a plant-based diet instead of an animal-based diet. Moreover, this work has already demonstrated the environmental impacts meat consumption brings.…”
Section: Discussionmentioning
confidence: 99%
“…Negative framing emphasizes the adverse consequences of not performing behaviors [60,61]. In the case of negatively framed separation messages, the contents are mostly textual or pictorial messages about environmental destruction and threats to human health, which could trigger negative emotions [22,62,63].…”
Section: Effect Of Negative Message Framing On Waste Separation Willi...mentioning
confidence: 99%